Texting Brief Podcasts to Deliver Faculty Development to Community-Based Preceptors in Longitudinal Integrated Clerkships - Joshua Bernstein; Lindsay Mazotti; Tal Ann Ziv; Joanna Drowos; Sandra Whitlock; Sarah K. Wood; Shelley L. Galvin; Robyn Latessa (Association of American Medical Colleges, 2018)
Introduction Longitudinal integrated clerkships (LICs) are an increasingly popular clerkship model that relies heavily on community-based preceptors. The availability of an engaged and prepared community-based faculty is crucial to the success of these programs. Teachers in these programs are often geographically separate from medical school campuses, are engaged in busy practices, and have limited time to devote to faculty development activities. Methods We created a series of five brief faculty development podcasts directed towards community-based teachers in LICs from three US medical schools. Topics included encouraging continuity, bedside teaching, encouraging student ownership of patients, communicating and managing patient results between clinic days, and choosing the right patients for continuity. The podcasts were sent via a grouped text message just prior to preceptors' morning commute time. Pre- and postsurveys assessed the acceptability and effectiveness of the podcasts. Results Among the 33 postintervention survey responders, 27 (81.8%) listened to at least three podcasts, 21 (63.6%) found them moderately or very helpful, 23 (69.7%) perceived that the podcasts altered their teaching style, 23 (69.7%) would likely or highly likely listen to further podcasts, and 18 (54.5%) would likely or highly likely recommend the podcasts to colleagues. Discussion In a cohort of multispecialty faculty teaching in LICs, educational podcasts were well received and perceived by preceptors to impact their teaching style. Texting these podcasts to other community-based preceptors may offer an effective strategy for providing faculty development to busy clinicians.